(untitled) (Devenires, 2012)
Bold and insolent, unequivocally tragic, war displays the logic of the worst and yet has behind it the aura of honour, the pathos that has immemorialy accompanied this form of profit. The hero, the saint and the genius are part of a trilogy presented as forms of exemplary humanity of which, rarely, the assumptions that consecrate it are investigated and that theology, the singing of deeds or works of art usually cover up behind their charms. In particular, the warlike rage has given rise to the construction of a symbolism of power without regard to the abysses or the means available for victory.